COMP Report: A survey of radiation safety regulations for medical imaging x‐ray equipment in Canada. Issue 3 (20th September 2019) - Bjarnason, Thorarin A.; Rees, Robert; Kainz, Judy; Le, Lawrence H.; Stewart, Errol E.; Preston, Brent; Elbakri, Idris; Fife, Ingvar A. J.; Lee, Ting‐Yim; Gagnon, I Martin Benoît; Arsenault, Clément; Therrien, Pierre; et al.
Abstract: X‐ray regulations and room design methodology vary widely across Canada. The Canadian Organization of Medical Physicists (COMP) conducted a survey in 2016/2017 to provide a useful snapshot of existing variations in rules and methodologies for human patient medical imaging facilities. Some jurisdictions no longer have radiation safety regulatory requirements and COMP is concerned that lack of regulatory oversight might erode safe practices. Harmonized standards will facilitate oversight that will ensure continued attention is given to public safety and to control workplace exposure. COMP encourages all Canadian jurisdictions to adopt the dose limits and constraints outlined in Health Canada Safety Code 35 with the codicil that the design standards be updated to those outlined in NCRP 147 and BIR 2012.